And the Dish Ran Away with the Spoon - Janet Stevens (Boston, United States Houghton Mifflin Harcourt Publishing Company, 2016)
d
Keywords: Circle Time; Traditional Literature & Fairytales/ Folklore Myths & Legends / Fables -- Traditional Literature & Fairytales/ Folklore Myths & Legends / Fables